Use of a combined SIEA and SCIP based double pedicled abdominal flap for breast reconstruction. Issue 4 (7th March 2021) - Yano, Tomoyuki; Yoshimatsu, Hidehiko; Karakawa, Ryo; Fuse, Yuma; Kuramoto, Yukiko; Shibata, Tomoyoshi; Suesada, Nobuko; Miyashita, Hiroki
Abstract: Background: Recently, the deep inferior epigastric perforator (DIEP) flap has become the gold standard for breast reconstruction, but it has some drawbacks such as abdominal bulging and hernia. To overcome these disadvantages, the superficial inferior epigastric artery perforator (SIEA) flap is used as an alternative option, but it has another problem, namely limited vascular territory and risk of vascular thrombosis. To solve these problems, we introduced our new technique, a combined SIEA and superficial circumflex iliac artery perforator (SCIP) based double pedicled abdominal flap. In this report, we present our experience of using this technique. Methods: The SIEA and SCIP based double pedicled abdominal flap was used in five patients who wanted to have unilateral breast reconstruction after a mastectomy due to breast cancer. The average age was 48.2 (range 38–56) years, and the average BMI was 24.4 (range 19.2–31.4). The SIEA and SCIP based double pedicled abdominal flap was designed as a modified DIEP flap, and all flaps were placed in the vertical setting. The flap pedicles had two different vascular supplies, SIEA and SCIA, and the drainage systems, SIEV and SCIV, anastomosed to the internal mammary artery and vein in all cases. Results: The harvested SIEA and SCIP based double pedicled abdominal flaps were a median volume of 925 g (range 452–1570 g) and average size of 491 cm 2 (range 440–611 cm 2 ). The average reconstructive time was 7:41 (range 6:31–9:17). In four out of the five cases, the SIEA and SCIA joined together to make a common pedicle artery trunk, and its average size was 1.08 mm. Four out of the five cases had a wide vascular territory crossing the abdominal midline as shown by ICG angiography. One case showed ICG fluorescence for the hemi‐side of the abdominal flap. Postoperative course was uneventful, and there were no major perioperative complications, which need extra surgical procedures. Follow‐up period averaged 273 days (range 194–312 days). Conclusion: The SIEA and SCIP based double pedicled abdominal flap showed viable flap territory across the midline in all cases. The SIEA and SCIP based double pedicled abdominal flap might be another ideal option for breast reconstruction, when appropriate SIEA and SCIA pedicles are identified, and an adequate ICG fluorescence is obtained for the size of flap needed.